UJI AKTIVITAS ANTHELMINTIK EKSTRAK ETANOL DAUN PEPAYA PADA CACING GELANG BABI - Mahatriny, Ni Nyoman; Sanggra Payani, Ni Putu; Suwanti Devi, Pande Ketut; Yulita, Santri; Astuti, Ketut Widyani; Made Oka, Ida Bagus (Program Kreativitas Mahasiswa - Penelitian, 2014)
Papaya leaves ethanol extract was evaluated for anthelmintic activity on pig roundworm by in vitro assay. The aim of this research is to know whether papaya leaves ethanol extract has anthelmintic activity and to determine LC100 and LT100 values of papaya leaves ethanol extract. Anthelmintic activity test was done by using 7 groups with 3 repetition. Group I soaked in CMC-Na 0,5% as control negative; group II soaked in albendazole suspense 0,6% as control positive; groups III-VII soaked in papaya leaves ethanol extract suspense (0,6%; 1,2%; 2,4%; 4,8%; and 9,6% respectively) for 40 hours. Observation was done every 2 hours to know mortality of pig roundworm. Percentage of pig roundworm mortality were analyse by Kruskal-Wallis test along with Mann-Whitney test. LC100 and LT100 value was determine using corrected probit analysis. Papaya leaves ethanol extract at dosage 1,2%; 2,4%; 4,8%; dan 9,6% has a anthelmintic activity because gives a significant value in mortality of pig roundworm if compare with control negative (p<0,05). From corrected probit analysis papaya leaves ethanol extract has LC100 in 8,301% b/v and LT100 in 28,885 hours.    Keywords:  Anthelmintic, Papaya leaves, LC100, LT100.